1959
DOI: 10.1136/hrt.21.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Digoxin on the Circulation in Normal Man

Abstract: Digitalis is one of the oldest and most widely used drugs in clinical medicine. Its action in congestive cardiac failure has been thoroughly studied by many workers. Its action upon the normal circulation, however, has received relatively little attention. The concept that it lowers cardiac output and reduces central venous pressure in normal subjects continues to be expressed by many workers. This view, based on studies employing older, often inadequate methods, has been neither confirmed nor disproved by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[51]. Consistently, no drug-related adverse events have been reported in trials on subjects with normal hearts who were given clinical doses of ouabain [52,53], digitoxin [23,54], or digoxin [55][56][57][58]. Nonetheless, it is important that treatment with these drugs should always be under the control of health care professionals.…”
Section: Discussionmentioning
confidence: 92%
“…[51]. Consistently, no drug-related adverse events have been reported in trials on subjects with normal hearts who were given clinical doses of ouabain [52,53], digitoxin [23,54], or digoxin [55][56][57][58]. Nonetheless, it is important that treatment with these drugs should always be under the control of health care professionals.…”
Section: Discussionmentioning
confidence: 92%
“…The ability of digitalis to increase the force of myocardial contraction was first demonstrated in depressed cat papillary muscles in 1938, by Catell and Gold, but the techniques available at that time failed to demonstrate consistently a similar effect in non-depressed cardiac muscles (Catell and Gold, 1938;White and Salter, 1946). Haemodynamic studies undertaken after the introduction of cardiac catheterization showed either no change or a decrease in cardiac output in animals or humans not in cardiac failure (McMichael and Sharpey-Schafer, 1944;Williams, Zohman and Ratner, 1958;Selzer, Hultgren and Ebnother, 1959). These results led to the belief that digitalis stimulated the failing myocardium, but did not increase contractility in the normal heart.…”
Section: Cardiac Glycosidesmentioning
confidence: 99%
“…At first it was considered advisable, particularly for the high‐risk elderly patient; later it was deplored, especially for this type of patient if no heart failure was present, the reasons being that it was harmful and did not produce any improvement in cardiodynamics. Selzer et al (3) recently demonstrated that though the contractile force of the hypertrophied compensated heart is increased, the cardiovascular homeostatic mechanisms seem to keep the cardiac rate and output, the blood pressure, and the coronary arterial blood flow at normal levels; in the same way, any increased contractile force resulting from the inotropic action of digitalis is prevented from producing supernormal dynamic effects. It is interesting to speculate about the prophylactic use of digitalis preoperatively in cases of “presbycardia”without heart failure; the stress and shock of surgery might be better tolerated, for instance, in the patient whose initially normal cardiac output suddenly falls below the optimal level.…”
Section: Digitalismentioning
confidence: 99%